MENANAMKAN KARAKTER BIRRUL WALIDAIN PADA ANAK USIA DINI - Amalia Nurul Khasanah (QURROTI, 2022)
The thing that is important or urgent to be applied today, character planting must be carried out from an early age, where the child will experience a change in orientation with the formation of the child. Seeing the rise of a world that is not regulated by regulations makes the younger generation lose their world. In this context, the role of parents is very much needed for character building from an early age. To what extent is the planting related to Birrul Walidain given, the results will be that big. So that it can be necessary to invest more deeply related to the formation of the character of Birrul Walidain in early childhood. The purpose of this research is to study about instilling the character of Birrul Walidain in early childhood. The research uses qualitative methods by using field research which aims to determine the accuracy of the data. The technique used is to collect data by observation, as well as structured interviews. The results obtained stated that children gain knowledge from what is known to children and with parents giving planting to be devoted to parents by means of training that contains elements of direction towards children. By starting character formation as early as possible in early childhood.